Threat Modeling - Recommendations for a Health Care Facility (Journal of Global Humanities and Social Sciences, 2025)
Seamless information exchange is crucial in healthcare due to the integration of computational systems. The increased use of Personally Identifiable Information (PII) in digital healthcare raises privacy and security concerns. Threat Modeling Methodologies (TMMs) have emerged to address these challenges by locating and resolving cyber security threats. Early implementation of TMMs equips organizations to combat breaches and understand potential attackers. Integrating techniques, these methodologies strengthen systems and create a comprehensive shield against cyber invasions. However, there is no universal fix for system flaws, necessitating continual adaptation of counter-strategies. Applying threat modeling enables consistent identification, quantification, and assimilation of threats. Determining the most effective approach during product development based on objectives remains challenging. The goal is to scale the chosen strategy effectively, adhere to reporting requirements, and gain valuable insights for enhanced security. This fortifies organizations to navigate the evolving cyber landscape, safeguard PII, and maintain trust.